PERUBAHAN SOSIAL MASYARAKAT KRAMAT TUNGGAK PASCA BERDIRINYA MASJID JAKARTA ISLAMIC CENTRE - Maila D.H. Rahiem; Cut Dhien Nourwahida (FISIP Universitas Malikussaleh, 2023)
Kramat Tunggak, which operated from 1970 to 1999, was Southeast Asia's largest prostitute district. Following the demise of the localization, an Jakarta Islamic Centre (JIC) mosque was built. Changes in the function of the area have an impact on the quality of life in the neighborhood. The research examined the social changes that have happened among the residents of Kramat. This study employed a descriptive qualitative methodology. The data was acquired through observation, in-depth interviews, and a review of relevant documents. Eight Kramat Tunggak locals, one Jakarta Islamic Centre Mosque manager, and one RT chair participated in this study. The study discovered that several social changes occurred in Kramat Tunggak following the establishment of the Islamic Centre Mosque. Kramat Tunggak's people have undergone social transformations: 1) increased comfort and security of the residential area, as well as the tranquility of the community in carrying out life activities; 2) creating new jobs for the community, particularly as traders; 3) increased community participation in religious activities; 4) the community is liberated to engage in activities and interact in the Kramat Tunggak neighborhood. Encouraged by these advances, the residents of Kramat Tunggak should continue to make excellent use of the Jakarta Islamic Centre Mosque and the resources it provides to improve their social, cultural, religious, and economic life.Kramat Tunggak, yang beroperasi dari tahun 1970 hingga 1999, merupakan lokalisasi pelacuran terbesar di Asia Tenggara. Menyusul ditutupnya lokalisasi, masjid Jakarta Islamic Centre dibangun. Perubahan fungsi kawasan berdampak pada kualitas kehidupan di lingkungan sekitar. Penelitian ini bertujuan untuk mengetahui perubahan sosial yang terjadi pada masyarakat Kramat Tunggak pasca berdirinya Masjid Jakarta Islamic Centre. Metode yang digunakan dalam penelitian ini adalah metode kualitatif deskriptif. Peneliti mewawancarai 8 orang masyarakat Kramat Tunggak, 1 orang pengurus Masjid Jakarta Islamic Centre dan 1 orang ketua RT. Perubahan sosial yang terjadi pada masyarakat Kramat Tunggak Pasca Berdirinya Masjid Jakarta Islamic Centre antara lain: 1) meningkatnya kenyamanan dan keamanan daerah tempat tinggal, serta ketenangan masyarakat dalam menjalankan aktivitas kehidupan; 2) memberikan wadah lapangan pekerjaan bagi masyarakat terutama sebagai pedagang dengan adanya masjid Islamic Centre; 3) meningkatnya partisipasi masyarakat dalam kegiatan keagamaan; dan 4) masyarakat menjadi lebih leluasa berkegiatan dan berinteraksi di sekitar wilayah Kramat Tunggak. Didorong oleh kemajuan ini, warga Kramat Tunggak harus terus memanfaatkan Masjid Islamic Centre dengan baik dan sumber daya yang disediakannya untuk meningkatkan kehidupan sosial, budaya, agama, dan ekonomi mereka.